2020
DOI: 10.1186/s12934-020-01342-z
|View full text |Cite
|
Sign up to set email alerts
|

Current developments on polyhydroxyalkanoates synthesis by using halophiles as a promising cell factory

Abstract: Plastic pollution is a severe threat to our environment which necessitates implementation of bioplastics to realize sustainable development for a green world. Polyhydroxyalkanoates (PHA) represent one of the potential candidates for these bioplastics. However, a major challenge faced by PHA is the high production cost which limits its commercial application. Halophiles are considered to be a promising cell factory for PHA synthesis due to its several unique characteristics including high salinity requirement p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
80
0
13

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(103 citation statements)
references
References 143 publications
(254 reference statements)
0
80
0
13
Order By: Relevance
“…Indeed, it is reported that the major drawbacks faced by haloarchaea species, such as Hfx. mediterranei , are the low PHA productivity resulted from slow growth rate and failing to achieve high cell-density cultivation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, it is reported that the major drawbacks faced by haloarchaea species, such as Hfx. mediterranei , are the low PHA productivity resulted from slow growth rate and failing to achieve high cell-density cultivation [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…To maintain the optimal osmotic conditions for Hfx. mediterranei [ 37 ], the R-UF fraction was supplemented with NaCl. According to previous findings [ 37 ] the high salt concentration allowed to carry out the experiments in non-sterile conditions.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The main advantages of these materials include nontoxicity, biodegradability, plasticity, and selective gas permeability [ 43 , 44 ]. Meanwhile, the major drawbacks of microbial polymers that limit their competitiveness in commercial food packaging applications are both high production costs and relatively poor mechanical properties [ 44 , 45 ]. Currently, polyhydroxyalkanoates are mostly used as a packaging material for food with high oil content (e.g., olives, cheese, nuts), frozen, oxygen-sensitive, as well as organic products [ 18 , 46 , 47 , 48 ].…”
Section: The Market Of Bio-based Packagingsmentioning
confidence: 99%